Sustainability In NFT: Discrepancies Between The Discussion and Actualization Of Environmental Friendly NFT - Muhammad Lukman Baihaqi Alfakihuddin; Feby Theresia; Aurelia Adyarini Kacaya; Innaya Putri Munandar (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
As the globe faces difficulties in 2019, NFT grew popular in making, buying, selling, and trading more efficient while lowering the possibility of fraud. [1] This study aims to examine the claims made in academic literature regarding the sustainability of non-fungible tokens for the environment. Despite the growth of NFTs in 2019, the environmental impact of this technology has received little attention. Using a qualitative exploratory approach, this research analyzes relevant academic journals to understand the theoretical sustainability of NFTs and how that aligns, or fails to align, with the reality. The goal is to raise awareness about the environmental implications of NFTs and provide a critical assessment of the existing claims surrounding their sustainability.